Effect of electron irradiation on the electrical and optical characteristics of gallium-nitride light emitting diodes - Hedzir, Anati Syahirah; Muridan, Norasmahan; Yusof, Abdullah; Hasbullah, Nurul Fadzlin (Vlokh Institute of Physical Optics, 2019)
We study the effect of electron irradiation on the electrical and optical characteristics of commercial gallium-nitride light emitting diodes in the fluence region from 1015 to 1017 electrons/cm2. After electron irradiation, the forward leakage current shows no significant changes, while the reverse-leakage current increases twice under the fluence 9.90×1016 electrons/cm2. This suggests the existence of radiation damage-induced traps. The irradiation reduces the capacitance and the carrier concentration, which can be attributed to deactivation of dopant atoms. Basing on electroluminescence measurements, we prove that the luminescence intensity and the red shift of peak position increase significantly with increasing dose. The peak-wavelength shift can be attributed primarily to the radiation-induced defects that cause formation of red bands and, at the same time, gradually suppress the band-edge luminescence.